2011
DOI: 10.1227/neu.0b013e31823020e6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Diffusion Tensor Magnetic Resonance Imaging-Based Tractography for Surgery of Gliomas Near the Pyramidal Tract

Abstract: DT imaging-based fiber tracking is a reliable and accurate method for mapping the course of subcortical PTs. Fiber tracking and intraoperative MEPs were useful for preserving motor function in patients with gliomas near the PT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 47 publications
5
70
0
11
Order By: Relevance
“…Использова-ние данных предоперационной ДТ-трактографии с интеграцией их в нейронавигационную систему по-зволяет во время резекции опухоли визуализировать расстояние от тракта до инструмента. Однако при этом могут возникать неточности из-за смещения мозговых структур [7,23]. В связи с этим прямая ЭС остается основным методом выбора для оценки ло-кализации ПТ в хирургии внутримозговых опухо-лей.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Использова-ние данных предоперационной ДТ-трактографии с интеграцией их в нейронавигационную систему по-зволяет во время резекции опухоли визуализировать расстояние от тракта до инструмента. Однако при этом могут возникать неточности из-за смещения мозговых структур [7,23]. В связи с этим прямая ЭС остается основным методом выбора для оценки ло-кализации ПТ в хирургии внутримозговых опухо-лей.…”
Section: Discussionunclassified
“…При маленькой силе тока (1-3 мА) при прямой субкортикальной ЭС только у 23 из 67 пациентов не отмечалось перма-нентных неврологических нарушений в послеопе-рационном периоде, что связано с большим объ-емом резекции у данной категории пациентов [39]. Как известно, сила тока имеет прямую взаимозави-симость с расстоянием, на которое он распростра-няется, с примерным соотношением 1 мм -1 мА («золотое правило» нейрофизиологии) [23,[40][41][42].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…We start with an initial stimulation intensity of 10-15 mA, which corresponds to about 10-15 mm from the CST. 16,27,28,30,38 The instant an MEP is elicited, the surgeon is immediately alerted by the change of the high-pitch negative control sound to a low-pitch alert sound. The stimulation intensity is then reduced in 2-mA steps, allowing the surgeon to continue tumor removal until another low-pitch alert sound indicates that resection is getting closer to the CST.…”
Section: Intraoperative Handling Of the Continuous Dynamic Mapping Dementioning
confidence: 99%
“…16,19,27 As a rule of thumb, 1 mA of current corresponds to 1 mm remaining distance to the CST. 27,28 We previously demonstrated a safe window between high and low MTs for mechanical injury to the CST and showed that significant signal changes in MEP monitoring and permanent motor deficits do not occur above very low MTs of less than 1-2 mA. 38 These data also support the hypothesis that insufficient spatial and temporal coverage of the surgical site due to use of an interruptive and punctiform mapping technique may contribute to motor deficits despite higher and apparently safe MTs (3-6 mA).…”
mentioning
confidence: 99%